Simulasi Kebutuhan Air untuk Tanaman Padi Pada Skenario Perubahan Iklim di Daerah Aliran Sungai Lembang-Sumani - Sugeng Nugroho, Rudi Febriamansyah, Eri Gas Ekaputra, Dodo Gunawan (Jurnal Sumber Daya Air)
An impact of climate change is very significant effect on the agricultural sector, because sustainability of agriculture absolutely depends on climate conditions. The climate change that occurs in an area is highly depend on the sensitivity of local factors in responding to global climate change, so it is important to do correction of global climate change data with on-site observation data. CDFDM is one of the bias correction methods that can be used to make such orrections. Water requirements for crops and irrigation are calculated using the CROPWAT model. The results of the analysis showed that the projection of climate element in the research location shows that in general has increased. The greatest increase in rainfall is up to 47.5% by 2040 if the climate changes with the RCP8.5 scenario and the average increases between 18-20% in 2020-2040, both on scenes RCP4.5 and RCP8.5. Air temperature will increase between 4-6% in 2020-2040 on scenario RCP4.5 and RCP8.5. The largest increase in air temperature per decade was 8.1% by 2040 on the RCP8.5 scenario. The projection of water demand for crops in general has increased in line with the higher rainfall and air temperature projections, except for Sumani study sites, which experienced a deficit in rainfall requirements, which required irrigation water, in the May-August planting season.